Serum Creatine Kinase as Early Predictor of Necrotizing Enterocolitis in Rats - Quispe Orejón, Carmen (1999)
OBJECTIVE: To assess serum variations of creatine kinase in an experimental model of necrotizing enterocolitis. MATERIAL AND METHODS: Serum levels of creatine kinase were measured before and 2, 4 and 6 hours after a selective occlusion of vessels in the mesenteric vascular arcades in albine Wistar rats at the Experimental Surgery Department, Instituto de Salud del Niño. RESULTS: Baseline level obtained was 3304 U/L. Serum levels of total creatine kinase varied in the six-hours period, showing a marked increase in the first two hours (mean = 6333 U/L) and slowly decreased by the fourth hour (mean = 5766 U/L) and by the sixth hour (mean = 4284 U/L); although it did not either achieve the baseline values nor decline below it again. CONCLUSIONS: Our results suggests that selective occlusion of vessels in the mesenteric vascular arcades during a 6-hours-period, produces changes similar to those observed in necrotizing enterocolitis, and results in an increase of creatine kinase levels when the involvement is consistent with grade III human necrotizing enterocolitis, but these increase was non-significant.